2007
DOI: 10.1152/japplphysiol.00420.2007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of promoter region variants of insulin-like growth factor pathway genes on the strength-training response of muscle phenotypes in older adults

Abstract: To examine the influence of insulin-like growth factor (IGF) pathway gene polymorphisms on muscle mass and strength responses to strength training (ST), we studied 128 White and Black men and women before and after a 10-wk single-leg knee extension ST program. One-repetition maximum strength, muscle volume (MV) via computed tomography, and muscle quality (MQ) were assessed at baseline and after 10 wk of ST. There was a significant combined IGF1 cytosine adenine (CA) repeat gene effect, which included both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 61 publications
2
34
1
1
Order By: Relevance
“…Such a trade‐off is consistent with reports regarding IGF‐1, a key hormone regulated by growth hormone. Individuals with IGF1 variants associated with high IGF‐1 blood levels gain more strength following resistance training (Hand et al, 2007; Kostek et al, 2005). Yet, genetic polymorphisms in the gene for IGF‐1 receptor, which result in decreased IGF‐1 plasma levels, associate with longevity (Bonafe et al, 2003; Suh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Such a trade‐off is consistent with reports regarding IGF‐1, a key hormone regulated by growth hormone. Individuals with IGF1 variants associated with high IGF‐1 blood levels gain more strength following resistance training (Hand et al, 2007; Kostek et al, 2005). Yet, genetic polymorphisms in the gene for IGF‐1 receptor, which result in decreased IGF‐1 plasma levels, associate with longevity (Bonafe et al, 2003; Suh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous resistance training studies in humans have used the 1 RM as a method of determining the effect of resistance training on muscle strength (Charbonneau et al 2008;Hand et al 2007;Hubal et al 2005;Kostek et al 2005;Riechman et al 2004). However, although the 1 RM is a relatively simple task to perform, it involves not just the intrinsic strength of the muscle group but also the actions of synergistic and stabilizing muscles (Rutherford and Jones 1986), thus questioning its suitability for detailed physiological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Hand et al (2007) recently reported that the insertion/deletion (I/D) polymorphism of PPP3R1 gene, or at least its interaction with IGF1 CA repeat, may inXuence the training responsiveness of muscle strength. The PPP3R1 I/D polymorphism was also associated with left ventricular hypertrophy in hypertensive patients (Tang et al 2005) and athletes (Akhmetov et al 2008).…”
Section: Introductionmentioning
confidence: 99%